Global, Regional, and National Burden of Breast Cancer in Adolescents and Young Adults Aged 15–39 Years From 1990 to 2021 Based on the Global Burden of Disease Study 2021 - Zheng Qu; Zheng Li; Shengbin Pei; Ye Lu; Qiang Liu; Peikai Ding; Yazhe Yang; Luxiao Zhang; Jing Wang; Yi Fang (Cancer Innovation)
ABSTRACT Background Breast cancer (BC) remains a significant global public health challenge, and its incidence and mortality rates among adolescents and young adults (AYAs) aged 15–39 years are increasing. Compared with older adults, AYAs often face poorer prognoses and a higher disease burden. Understanding the trends and determinants of BC burden in AYAs is crucial for guiding preventive measures, early detection programs, and treatment strategies. The aim of this study is to systematically investigate the trends and distribution of the BC burden among AYAs aged 15–39 years across regions and countries and identify the contributing risk factors and disparities in incidence, mortality, and disability‐adjusted life years (DALYs). Methods Data on BC were collected from the Global Burden of Disease (GBD) 2021 database. The number of cases, age‐standardized rates, mortality, and DALYs for BC were assessed for 204 countries and territories from 1990 to 2021. Joinpoint regression analysis was used to calculate the average annual percentage changes (AAPCs) in incidence, mortality, and DALYs. Risk factors that contribute to the BC burden were also evaluated. Results According to GBD 2021 estimates, 180,791 new BC cases and 42,055 related deaths were observed among AYAs globally. Between 1990 and 2021, the global incidence rate increased by 33.4%, with the highest incidence observed in regions with a high sociodemographic index (SDI) and the highest mortality rates in low‐SDI regions. Incidence rates in women showed a significant upward trend (AAPC, 3.03) and peaked in North Africa and the Middle East, whereas the most rapid increase in incidence in men was noted in East Asia (AAPC, 4.87). Projections indicated a decline in age‐standardized incidence rates across most European countries by 2050, in contrast to rising trends in Asia and Africa. Risk factor analysis identified dietary risks (10.5%), tobacco smoking (2%), and high fasting plasma glucose (1.6%) as major contributors to DALYs. Conclusions The global burden of AYA BC has increased significantly, particularly in regions with a middle and low SDI. The findings highlight the need for targeted preventive interventions for high‐risk populations and provide critical insights for developing regional control strategies.